1999
DOI: 10.7164/antibiotics.52.466
|View full text |Cite
|
Sign up to set email alerts
|

Sanglifehrins A, B, C and D, Novel Cyclophilin-binding Compounds Isolated from Streptomyces sp. A92-308110. I. Taxonomy, Fermentation, Isolation and Biological Activity.

Abstract: A novel class of macrolides for which the name sanglifehrins is proposed, has been discovered from actinomycete strains based on their high affinity binding for cyclophilin A (CypA), an immunophilin originally identified as a cytosolic protein binding cyclosporin A (CsA). The sanglifehrins were produced by Streptomyces sp. A92-3081 10. They were isolated and purified by extraction and several chromatographic, activity-guided steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
101
0
2

Year Published

1999
1999
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 17 publications
1
101
0
2
Order By: Relevance
“…These results clearly distinguish SFA from other known cytotoxic DNA damaging drugs and indicate that SFA is a unique agent that interacts with immunophilins on the one hand and activates NFB and p53 on the other without causing DNA damage. DISCUSSION SFA was discovered as a novel immunosuppressive agent (19,20). It was recently shown that SFA blocks IL-2-dependent T cell proliferation at the G 1 phase of the cell cycle, similar to FIG.…”
Section: P53 Is An Important Mediator Of Inhibition Of Cell Proliferamentioning
confidence: 99%
See 2 more Smart Citations
“…These results clearly distinguish SFA from other known cytotoxic DNA damaging drugs and indicate that SFA is a unique agent that interacts with immunophilins on the one hand and activates NFB and p53 on the other without causing DNA damage. DISCUSSION SFA was discovered as a novel immunosuppressive agent (19,20). It was recently shown that SFA blocks IL-2-dependent T cell proliferation at the G 1 phase of the cell cycle, similar to FIG.…”
Section: P53 Is An Important Mediator Of Inhibition Of Cell Proliferamentioning
confidence: 99%
“…Unlike CsA, however, the cyclophilin-SFA complex has no effect on the phosphatase activity of calcineurin (21). Although SFA was shown to inhibit mouse and human mixed lymphocyte reactions (19), we and others have recently found that SFA does not affect T cell receptor-mediated signal transduction pathways leading to the production of cytokines such as IL-2 (21,22). Instead, SFA inhibits IL-2-dependent T cell proliferation, similar to rapamycin (23,24).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…S anglifehrins, described originally by Sanglier et al (1,2), are novel immunophilin-binding immunosuppressants with an unknown mechanism of action that are produced by the actinomycetes strain Streptomyces A92-308110. The immunophilin-binding agent cyclosporin A (CsA) 3 binds to cyclophilin and inhibits activity of the calcineurin phosphatase, whereas both FK506 and rapamycin (Rapa) bind to the FK506 binding protein but inhibit two different effector proteins: calcineurin phosphatase and mammalian target of Rapa (mTOR), respectively (3,4).…”
mentioning
confidence: 99%
“…Although Sanglifehrin A (SFA), like CsA, binds with high affinity to cyclophilin, unlike the latter, SFA does not inhibit calcineurin phosphatase activity (5). SFA has been reported to exhibit lower immunosuppressive activity in the MLR when compared with CsA (1,5). Studies of the immunosuppressive effects of SFA have been focused on T and B lymphocytes (5,6).…”
mentioning
confidence: 99%